2016
DOI: 10.5152/turkpediatriars.2016.3702
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of pomegranate juice in paracetamol-induced acute hepatotoxicity in rats

Abstract: Aim: Being the most commonly used antipyretic and analgesic, paracetamol is one of the most common causes of childhood poisoning in the world and maintains its importance also in our country. Paracetamol poisoning is one of the most common causes of liver failure. This study aimed to investigate if pomegranate juice had protective effect in acute liver toxicity related with paracetamol. Material and Methods:A total of 36 Wistar-Albino rats were divided into four groups as the paracetamol group (3 000 mg/kg par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Therefore, eliminating the effect of oxidation that is caused by its active metabolite is one of the most important measures. Several studies have been conducted to investigate its antioxidant effects . On the other hand, studies have shown that, contrary to the toxic and destructive effects of acetaminophen, there are compounds that can inhibit the toxicity of such drugs to some extent by eliminating free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, eliminating the effect of oxidation that is caused by its active metabolite is one of the most important measures. Several studies have been conducted to investigate its antioxidant effects . On the other hand, studies have shown that, contrary to the toxic and destructive effects of acetaminophen, there are compounds that can inhibit the toxicity of such drugs to some extent by eliminating free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to investigate its antioxidant effects. 26 On the other hand, studies have shown that, contrary to the toxic and destructive effects of acetaminophen, there are compounds that can inhibit the toxicity of such drugs to some extent by eliminating free radicals. One can mention antioxidants in medicinal plants as such compounds.…”
Section: ■ Discussionmentioning
confidence: 99%